Functional Food - Improve Health Through Adequate Food 2017
DOI: 10.5772/intechopen.68862
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols: Food Sources and Health Benefits

Abstract: The current scientiic knowledge on the relationship between diet and human health is greatly focused on the efects of phytochemicals, especially polyphenols, on chronic diseases, due to their preventive efect as shown by many epidemiological studies. Herbs, cocoa products, and darkly colored berries, such as black elderberries, chokeberries, and black currants, are the richest dietary sources that contribute to the average intake of polyphenols of about 1 g/day. Polyphenols that are the most common in the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Additionally, the simple form of polyphenols (monomeric ones) is formed from the degradation of the complex form of polyphenols (polymeric ones) under the simulated in vitro digestion . [50] Similarly, [51] obtained higher values of TPC in whole grains, including oat, subjected to in vitro digestion, and attributed this impact to the release of phenolic acids bound to proteins. Besides, the release of large amounts of peptides with aminophenol amino acid (tyrosine, tryptophan) and/or sulfur amino acid (cysteine), which could react with the Folin-Ciocalteu's reagent, may participate in obtaining higher values of TPC.…”
Section: Polyphenols Stability Of Gmy After In Vitro Digestionmentioning
confidence: 95%
“…Additionally, the simple form of polyphenols (monomeric ones) is formed from the degradation of the complex form of polyphenols (polymeric ones) under the simulated in vitro digestion . [50] Similarly, [51] obtained higher values of TPC in whole grains, including oat, subjected to in vitro digestion, and attributed this impact to the release of phenolic acids bound to proteins. Besides, the release of large amounts of peptides with aminophenol amino acid (tyrosine, tryptophan) and/or sulfur amino acid (cysteine), which could react with the Folin-Ciocalteu's reagent, may participate in obtaining higher values of TPC.…”
Section: Polyphenols Stability Of Gmy After In Vitro Digestionmentioning
confidence: 95%
“…Polyphenols, organic bioactive compounds known as secondary metabolites of plants are of considerable physiological and morphological importance in plants. In the last century, several clinical and epidemiological studies revealed that they possess a strong antioxidant capacity and anti-inflammatory properties that could have preventive or/and therapeutic effects for degenerative diseases, cardiovascular diseases, neurodegenerative disorders, cancer, obesity and food allergy (Kobernick and Burks, 2016;Mrduljaš et al, 2017;Cory et al, 2018;Gullón et al, 2020). Given these health benefits, the determination and characterization of polyphenols in foods to evaluate their bioavailability and bioactivity is becoming one of the most important research areas in food analysis (Lucci et al, 2017;Perez-Gregorio and Simal-Gandara, 2017).…”
Section: Past Present and Future In Polyphenols Upcyclementioning
confidence: 99%
“…Only resveratrol is considered important to human health, being grape skins, red wine, peanuts, blueberries and cranberries the main sources of this compound. Pterostilbene, a compound chemically related to resveratrol, is also found in grapes and blueberries; due to high antioxidant capacity, it is also considered important to human health (Mrduljaš et al, 2017).…”
Section: Stilbenesmentioning
confidence: 99%
“…Strategies for CH 4 mitigation that have been evaluated are varied and include the inoculation of exogenous bacterial strains [13], vaccine development, biological control, prebiotics, probiotics [6], defaunation (protozoa or methanogens), and the identification of natural compounds in plants used as feed additives [14]. These are not always applicable in practice and the results of some strategies have shown some variability [15], with variation attributed to the concentration of the compound of interest in the foliage, pods, or extracts, interaction or agonistic compounds, growth stage, climate conditions, manipulation compounds, in vitro or in vivo experiments, daily intake, and bioavailability [16,17]. Dietary manipulation is of relevance because the diet of animals has a great influence on the production of methane [3,10,18]; therefore, in the last decade, more intensive research on natural compounds for livestock has increased with the objective of reducing rumen CH 4 without affecting rumen fermentation and energy utilization mainly in in vitro trials [19,20].…”
Section: Introductionmentioning
confidence: 99%